Identification of Coloring Additives used in Jajan Sirat Production Sold at Pasar Umum Negara, District of Negara, Jembrana Regency, Bali Province - Andika, I Komang Ari; Ina, Putu Timur; Putra, I Nengah Kencana (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 3 No 1 (2016), 2016)
This study aimed to identify the types and doses of coloring additives used in the making of jajan Sirat which was sold at Pasar Umum Negara, Jembrana, Bali. Before taking samples, surveys and interviews were conducted to the traders and consumers regarding their understanding on coloring additives. The samples were taken from some traders at Negara public market, District of Negara, Jembrana, Bali. Then, the samples were prepared by using woolen thread absorption technique. Qualitative analytical procedure were conducted using chromatographic paper analysis, while quantitative analysis were conducted using spectrophotometer UV-VIS. Paper chromatography analysis showed, the samples contained restricted synthetic coloring substances (GN scarlet, orange G and sudan I) and allowed coloring substances (tartrazine, sunset yellow, karmoisin, amaranth, and eritrosin). Spectrophotometric analysis showed that most of samples contained coloring substances exceeding the prescribed dosage. The percentage of samples containing overdosed coloring substances was 58.33 %, whereas the percentage of samples containing coloring substances under permitted dosage was 16.67 %. The percentage of samples containing banned dye was 25.00 %.
Keywords: Jajan Sirat; Synthetic coloring additives; chromatography; spectrophotometric